2022
DOI: 10.33086/bfj.v7i1.2607
|View full text |Cite
|
Sign up to set email alerts
|

Gojek VS Grab: Which One Is Better in Creating Customer Satisfaction and Loyalty?

Abstract: Online ride-hailing is now becoming a popular option for customers to travel worldwide, including for consumers in Indonesia. However, the Covid-19 pandemic caused many force majeure problems for companies serving online ride-hailing services. These situations lead to numerous customer dissatisfaction, low switching cost, and disloyalty for customers to use online ride-hailing services. In particular, this study aims to investigate the comparison of customer satisfaction and loyalty level between Gojek and Gra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 18 publications
0
0
0
3
Order By: Relevance
“…Sastra baru-baru ini telah mengeksplorasi berbagai aspek yang mempengaruhi loyalitas pelanggan, menyoroti interaksi yang kompleks dari faktor-faktor yang membentuk perilaku konsumen. Studi telah menyelidiki dampak kualitas layanan (Wibawa et al, 2022), kepuasan pelanggan (E. , keterlibatan merek (Zaidun et al, 2021) dan kebijakan manajemen sumber daya manusia (Mitaši=unait.e, 2021) pada loyalitas pelanggan di berbagai industri dan konteks. Studi ini secara kolektif menyoroti sifat multi-faceted loyalitas pelanggan dan kebutuhan bisnis untuk mengadopsi pendekatan holistik dalam memahami dan menangani faktor-faktor yang mendorong loyalitas klien.…”
Section: Pendahuluanunclassified
See 2 more Smart Citations
“…Sastra baru-baru ini telah mengeksplorasi berbagai aspek yang mempengaruhi loyalitas pelanggan, menyoroti interaksi yang kompleks dari faktor-faktor yang membentuk perilaku konsumen. Studi telah menyelidiki dampak kualitas layanan (Wibawa et al, 2022), kepuasan pelanggan (E. , keterlibatan merek (Zaidun et al, 2021) dan kebijakan manajemen sumber daya manusia (Mitaši=unait.e, 2021) pada loyalitas pelanggan di berbagai industri dan konteks. Studi ini secara kolektif menyoroti sifat multi-faceted loyalitas pelanggan dan kebutuhan bisnis untuk mengadopsi pendekatan holistik dalam memahami dan menangani faktor-faktor yang mendorong loyalitas klien.…”
Section: Pendahuluanunclassified
“…Peningkatan e-commerce dan platform online telah mengubah cara bisnis berinteraksi dengan pelanggan, yang mengharuskan penilaian ulang strategi loyalitas tradisional. (Wibawa et al, 2022). Dalam konteks ini, memahami nuansa loyalitas pelanggan di era digital dan beradaptasi dengan perubahan preferensi dan perilaku konsumen telah menjadi prioritas bagi bisnis yang ingin berkembang di pasar yang kompetitif.…”
Section: Pendahuluanunclassified
See 1 more Smart Citation
“…During this pandemic, the quality of service sought byCustomers are more focused on the health protocols implemented by drivers and by the company. As a result, this is an impetus for GoRide services to maintain the quality of their services above their competitors while also exceeding the expectations of their customers (Sasono et al, 2021;Wibawa et al, 2022). Especially during this pandemic, it has become a natural thing for customers to expect services that are hygienic and comply with health protocols so that when they use GoRide services, they feel safe and avoid exposure to viruses.…”
Section: Introductionmentioning
confidence: 99%
“…Previous research also suggests conducting similar research in a cultural environment that is different from the geographical location of previous research (Ahmed et al, 2021). Not only that, research on ride-hailing passenger loyalty in Indonesia is so focused on two-wheeled ride-hailing services (GoRide and GrabBike), and rarely touches on the four-wheeled ridehailing market (Abadi et al, 2020;Irfianto, 2019;Wibawa et al, 2022). In addition, no quantitative research has been found that directly examines the relationship between switching costs and passenger loyalty for the fourwheeled ride-hailing market in Indonesia (Fu et al, 2018;Hadi et al, 2019;Samudro et al, 2018).…”
Section: Introductionmentioning
confidence: 99%